Genaro Vázquez y el movimiento social en Guerrero 1960-1963 - Castañeda Hernández, Pavel Alejandro (Universidad Michoacana de San Nicolás de Hidalgo, 2007)
On February 2, 1972, Mexico woke up with news of transcendental importance, newspapers and other publications from all over the country gave the information of the death of the then chief of the armed struggle in the country. Professor Genaro Vázquez Rojas had died suspiciously in the Civil Hospital of the city of Morelia after having injured the car in which he traveled with other civic people from Mexico City. The Federal Security Directorate (DFS), the army and the police of Guerrero and other states of the republic were behind them, on their heels. He was one of the men most required by the justice of his time. This event marked the end of the life of a man and an organization. It was the end of a long trajectory in the political opposition. It signified the collapse, the strongest blow to a revolutionary project built since Genaro Vázquez and other guerrerenses organized in opposition to the governor of Guerrero in 1960. The thesis that the reader has in his hands discerns the first years of life and work of the most important revolutionary organization of the sixties in Guerrero, the one that from April 1968 declared war on the PRI regime. Initially the investigation was considered as a biography of Genaro Vázquez Rojas. However, given the appearance of various sources and the modification of some hypotheses about the social movement in Guerrero, it was decided to give the research a spin. The result is an analysis that highlights an individual history with a series of political conjunctures in the years of 1960 to 1963. It will be observed that the first part of the first chapter privileges the biographical approach itself.

El 2 de febrero de 1972 México despertó con una noticia de trascendental importancia, periódicos y demás publicaciones de todo el país daban el dato del fallecimiento del entonces principal jefe de la lucha armada en el país. El profesor Genaro Vázquez Rojas había muerto sospechosamente en el Hospital Civil de la ciudad de Morelia después de haberse accidentado el carro en que viajaba junto a otros cívicos desde la ciudad de México. La Dirección Federal de Seguridad -DFS-, el ejército y las policías de Guerrero y otros estados de la república estaban tras ellos, pisándoles los talones. Era uno de los hombres más requeridos por la justicia de su tiempo. Este acontecimiento marcó el final de la vida de un hombre y una organización. Era el cierre de una larga trayectoria en la oposición política. Significó el derrumbe, el golpe más fuerte a un proyecto revolucionario construido desde que Genaro Vázquez y otros guerrerenses se organizaron en oposición al gobernador de Guerrero en 1960. La tesis que el lector tiene en sus manos discierne sobre los primeros años de la vida y obra de la organización revolucionaria más importante de los años sesenta en Guerrero, esa que a partir de abril de 1968 le declaró la guerra al régimen priísta. Inicialmente la investigación se planteó como una biografía de Genaro Vázquez Rojas. Sin embargo, ante la aparición de diversas fuentes y la modificación de algunas hipótesis sobre el movimiento social en Guerrero, se optó por darle a la investigación un giro. El resultado es un análisis que destaca una historia individual con una serie de coyunturas políticas en los años de 1960 a 1963. Se podrá observar que la primera parte del primer capítulo privilegia el enfoque biográfico propiamente dicho.
Instituto de Investigaciones Históricas. Facultad de Historia. Programa Institucional de Maestría en Historia
Keywords: info:eu-repo/classification/cti/4; IIH-M-2007-0004; Opción en historia de México; Genaro Vázquez; Movimiento social; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/2364